Between the countryside and the city: struggles for the right to an eminently peasant education - Naura Sthocco Silva; Helder de Moraes Pinto (Universidade Federal do Norte do Tocantins, 2021)
From a theoretical and interpretive perspective, the present article aims to discuss the socio-political context of the proposal for training teachers for Rural Education from the pressures of rural movements and the involvement of institutional partnerships. So, how did the socio-political process for the involvement of the state and institutions to promote the training of rural teachers? For this, we seek to present the differences between the educational realities offered in the rural areas and in the city in Brazil; to discuss the emergence of the demand for a specific peasant education as a process of resistance to agribusiness interests in the 20th century; and to present the insertion of the social demands of the rural areas in the guidelines of the state through Pronera and adhesion of the public Universities in the formation of rural teachers. The study is qualitative, explanatory and bibliographic having as the theoretical basis the Rural Education as a space for social struggle. As a result, it became evident that the political and institutional actions aimed at training teachers in the field took place as a product of the pressures of social movements, with due emphasis on the MST, along with the state and public institutions, which met the demands through articulation between Pronera and public universities. From this scenario, from the decade of the 1990s, Licenciatura do Campo courses emerged in response to the demands for teachers of specific training in rural schools, representing the increase in the representativeness of peasant wishes in the midst of debates on educational policies in Brazil. Advances that, due to the actions created during the first term of the Lula government, were established, giving continuity to new offers of vacancies in LeDocs courses in Brazil in the last decade.